Could a bio-resin and transparent pavement improve the urban environment? An in field thermo-optical investigation and life-cycle assessment. (April 2022) - Kousis, I.; Fabiani, C.; Pisello, A.L.
Abstract: Pavements affect the urban microclimate and the overall quality of the outdoor environment. Cool pavements, in particular, can guarantee lower surface temperature than conventional ones, e.g. asphalt and concrete. These solutions often comprise reflective coatings placed above existing pavements or more complex configurations, i.e. evaporative and heat harvesting solutions. This study investigates in-field the thermo-optical profiles of cool paving systems made with a novel modified epoxy resin binder. Unlike classic binders, the presented binder is transparent and, when combined with the proper aggregate minimizes its contribution to local surface overheating phenomena. The two novel fields presented herein were found to maintain up to 9.2 °C and 6.4 °C lower surface temperature during daytime and up to 8.4 °C and 4.6 °C lower surface temperature during nighttime as compared to the asphalt and concrete fields, respectively. A cradle-to-gate life cycle assessment showed that the novel binders may also decrease pavements' footprint on human health and ecosystems, while the application of a CO 2 off-set model showed their good potentiality to decrease the corresponding emissions. The novel binders, that unlike typical cool paving applications are an integral part of the pavement, are ready to be integrated in real life applications. Highlights: Novel reflective paving fields were developed by implementing transparent resin-based binders. Hygro-thermal/radiative profiles were extensively monitored during summer period. Maximum surface temperature reduction up to 9.2 °C/8.4 °C during daytime/ nighttime. The novel binder may decrease the overall environmental footprint of the pavement.